BUDI DAYA DAN ADAPTASI VARIETAS UNGGUL BARU PADI PADA LAHAN RAWA LEBAK SUMATERA SELATAN / Cultivation and Adaptation of New Superior Varieties Paady in Lebak Swampy Lands in South Sumatra - Suparwoto Suparwoto; Waluyo Waluyo (Badan Penelitian dan Pengembangan Pertanian, 2019)
Lebak swampy lands are one of the contributors to rice production in Indonesia, especially in South Sumatra. This agroecosystem is affected by river water overflow and rainfall. Based on the height and duration of waterlogging, the lebak swampy land is divided into three typologies, namely shallow lebak swampy lands, middle swampy lands, and deep swampy lands. This paper discusses cultivation and adaptation of new superior varieties of rice on lebak swampy lands. In this agroecosystem, rice is cultivated in the dry season after low tide, starting from shallow lebak swampy lands, then continuing to the middle lebak swampy lands and deep lebak swampy lands. Problems with rice cultivation on lebak swampy lands include: (1) stagnant water, (2) drought in the dry season, (3) continuous use of the same variety, (4) the use of poor quality seeds, (5) limited varieties superior, and (6) fertilizer use is not as recommended. Paddy cultivation in lebak swampy lands uses only local varieties such as Siputih which can be sown up to three times, so that the age of the seedlings can reach two months with high posture. Land preparation is carried out by cleaning weeds until they are ready for planting and using hand tractors in shallow and middle lebak swampy lands. The seed comes from its own multiplication (40 kg / ha). Ciherang and IR-42 varieties are used from season to planting season with fertilization according to the ability of farmers. Thus, the results obtained are low, ranging from 3.5-4.5 t / ha GKP. One way to improve rice productivity in lebak swampy lands is the use of new improved varieties. Inpara and Inpari varieties can grow and produce in shallow lebak swampy lands and middle lebak swampy lands. In shallow lebak swampy lands it is recommended to use drought tolerant varieties such as Situbagendit, Limboto, Batutegi, Inpago, Inpari-1, Inpari-4, Inpari-6, and Inpara-5. In deep lebak swampy lands, rice can only be cultivated once a year, using superior varieties in the long dry season. The recommended superior varieties are Inpara-3, Inpara-4, and Inpara-5 which are tolerant to soaking.Key words: Paddy, lebak swampy lands, superior varieties, cultivation, adaptation AbstrakLahan rawa lebak merupakan salah satu agroekosistem penyumbang produksi beras di Indonesia, terutama di Sumatera Selatan. Agroekosistem ini dipengaruhi oleh luapan air sungai dan curah hujan. Berdasarkan tinggi dan lama genangan air, lahan rawa lebak dipilah menjadi tiga tipologi, yaitu lebak dangkal, lebak tengahan, dan lebak dalam. Makalah ini membahas budi daya dan adaptasi varietas unggul baru padi pada lahan rawa lebak. Pada agroekosistem ini padi dibudidayakan pada musim kemarau setelah air surut, dimulai dari lebak dangkal, kemudian dilanjutkan pada lebak tengahan dan lebak dalam. Permasalahan budi daya padi pada lahan rawa lebak antara lain: (1) genangan air, (2) kekeringan pada musim kemarau, (3) penggunaan varietas yang sama secara terus-menerus, (4) penggunaan benih tidak bermutu, (5) keterbatasan varietas unggul, dan (6) penggunaan pupuk tidak sesuai anjuran. Budi daya padi pada lahan lebak dalam hanya menggunakan varietas lokal seperti Siputih yang dapat disemai sampai tiga kali, sehingga umur bibit bisa mencapai dua bulan dengan postur yang tinggi. Penyiapan lahan dilakukan dengan cara pembersihan gulma sampai siap tanam dan menggunakan traktor tangan pada lebak dangkal dan lebak tengahan. Benih berasal dari perbanyakan sendiri (40 kg/ha). Varietas Ciherang dan IR-42 digunakan dari musim ke musim tanam dengan pemupukan sesuai kemampuan petani. Dengan demikian, hasil yang diperoleh rendah, berkisar antara 3,5-4,5 t/ha GKP. Salah satu cara untuk memperbaiki produktivitas padi pada lahan lebak adalah penggunaan varietas unggul baru. Varietas Inpara dan Inpari dapat tumbuh dan berproduksi dengan baik pada lebak dangkal dan lebak tengahan. Pada lebak dangkal disarankan menggunakan varietas toleran kekeringan seperti Situbagendit, Limboto, Batutegi, Inpago, Inpari-1, Inpari-4, Inpari-6, dan Inpara-5. Pada lebak dalam, padi hanya dapat diusahakan satu kali dalam satu tahun, menggunakan varietas unggul pada musim kemarau panjang. Varietas unggul yang disarankan ialah Inpara-3, Inpara-4, dan Inpara-5 yang toleran rendaman.Kata kunci: Padi, rawa lebak, varietas unggul, budi daya, adpatasi.